2020
DOI: 10.3389/fmicb.2019.03122
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of High Pressure on Bacterial Spores Using Synchrotron Infrared Spectroscopy

Abstract: Bacterial spores are extremely resistant life-forms that play an important role in food spoilage and foodborne disease. The return of spores to a vegetative cell state is a three-step process, these being activation, germination, and emergence. High-pressure (HP) processing is known to induce germination in part of the spore population and even to inactivate a high number of Bacillus spores when combined with other mild treatments such as the addition of nisin. The aim of the present work was to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Furthermore, Fourier transform infrared (FTIR) spectroscopy is known to be of a great value in characterizing the cell metabolism and biochemical properties of some cell membrane components, such as lipids, proteins, and nucleic acid, etc. [17] . Given all the functional groups of these organic molecules absorb infrared light specifically, the structural and physiological alterations on the bacterial cells upon different stress could be studied by FTIR analysis [18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Fourier transform infrared (FTIR) spectroscopy is known to be of a great value in characterizing the cell metabolism and biochemical properties of some cell membrane components, such as lipids, proteins, and nucleic acid, etc. [17] . Given all the functional groups of these organic molecules absorb infrared light specifically, the structural and physiological alterations on the bacterial cells upon different stress could be studied by FTIR analysis [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Given all the functional groups of these organic molecules absorb infrared light specifically, the structural and physiological alterations on the bacterial cells upon different stress could be studied by FTIR analysis [18] . This technique has been applied to explore changes at cellular level of E. coli and Staphylococcus aureus upon plasma treatment [19] and the physiological state of Bacillus subtilis spores subjected to high pressure treatment [17] . However, to date, very few studies have reported the changes of cell membrane fluidity and potential under ultrasonic field.…”
Section: Introductionmentioning
confidence: 99%
“…These results confirmed the well-known findings that HPP treatments cause sublethal injuries on certain resistant microorganisms that are able to repair cellular damages due to pressure and recover their viability during storage, as reported elsewhere [ 28 , 29 ]. In this regard, it can be hypothesized that the resistant survivors detected in corn, wheat, and tapioca-starch-based HPP hydrogels could belong to pressure-resistant microbial subpopulations such as bacterial spores [ 30 ], which seemingly differ based on the type of starch source and should be addressed in further experiments. Bacterial spores are extremely resistant life forms triggered by stress scenarios such as high-pressure conditions, returning to active growth during storage at optimal temperature conditions such as 20 °C [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…This agent opens spores’ SpoVA channels for CaDPA, leading to rapid CaDPA release [ 84 ]. One final germinant is high hydrostatic pressure; pressures of 50–300 megaPascals trigger germination by directly activating IM GRs, while even higher pressures, 400–900 mPA, trigger the opening of the CaDPA channel in all spores that have been tested [ 85 , 86 ]. Dodecylamine, which is often used as a surfactant, and high pressure are not directly implicated in spore germination in the gut but are of importance in light of needs for spore eradication in hygiene and food processing.…”
Section: Sporulation and Germinationmentioning
confidence: 99%